Experimentation and model-based re-design for sustainable intensification of mixed crop-livestock smallholder farms in the Mixteca-Oaxaqueña region, Mexico - Reyna-Ramírez, Cristian Alejandro; Fuentes-Ponce, Mariela; Rossing, Walter A.H.; Groot, Jeroen C.J.; López-Ridaura, Santiago (Elsevier, 2025)
CONTEXT: Redesign of farm systems could enable smallholder farms to move towards sustainability. In farm redesign, the joint participation of researchers and farmers is fundamental, together with new techniques and tools for evaluation. OBJECTIVE: To apply and analyze the redesign mixed crop-livestock smallholder farms in the Mixteca-Oxaqueña region, Mexico, based on models and participatory experimentation, to propose more sustainable farm management alternatives. METHODS: Three mixed crop-livestock smallholder farms in the Mixteca-Oxaqueña region were redesigned, using models and participatory experimentation to test and assess more sustainable management alternatives. We used the FarmDESIGN model, which was parameterized, and allowed for the evaluation of the farms before and after on-farm experimentation with innovative cropping systems. The experimentation was co-designed based on an exploratory phase of pilot-experiments and in-depth discussions with farmers about the results, providing elements for the re-design of farms towards sustainability. The experiment results were inputs for the model to generate new alternatives. The cropping system experiments were conducted in collaboration with farmers over a two-year period. They consisted of i) polyculture with maize (Zea mays) and beans (Phaseolus vulgaris), ii) fodder mixture of oats (Avena sativa) and common vetch (Vicia sativa), and iii) improved fertilizer use for maize. RESULTS AND CONCLUSIONS: In the initial evaluation, the three analyzed farms showed precarious profitability with an annual income (profits) of USD$200 to USD$1000. The three farms had food autonomy and excess, and per hectare, covered the annual food requirements of 2 to 4 people. Proposals for the final design of the systems were based on explorations using data from the experiments. The proposed redesign responded to the need to increase income and improve the balance of organic material and nitrogen and to reduce greenhouse gas emissions. The proposals focused on increasing the sale of animals, reducing herd size, promoting grazing on farms, producing forage with irrigation in the dry season, and rational fertilization for the tomato, bean, and maize crops, considering their sales. Nevertheless, in addition to reconfiguring the farm systems, public policies are necessary that create distribution mechanisms for the food produced and new value chains are necessary, as well as the provision of technical support for animal management, and fertilization schemes for high commercial value crops for human and animal consumption. SIGNIFICANCE: This study successfully included the interaction with farmers and the combination of an experimental and model-based analysis. We were able to adapt to the current conditions of the study area by working individually with each of the three farms. These farms are nevertheless indicative and provide elements for agrosystem redesign for greater agricultural activity in the region. New configurations resulting from the farm modeling and experimentation responded to the need to increase income and food autonomy, without increasing the environmental impact and labor.